Disrupting Homelessness: Alternative Christian Approaches - Bowpitt, Graham (A journal of church and state, 2011)
This book is an attempt to bring Christian theological insights into debates about homelessness. Although written by a North American academic, its reflections will resonate with anyone who has a passion to understand and improve the lives of homeless people in developed, democratic societies. The author nevertheless directs her attention at a field of social involvement in which, in the case of the United States, Christian bodies play a very large part, either as churches or voluntary organizations, and the book is undoubtedly written with them in mind.